Photosynthetic Adaptation of the Green Alga Chlamydomonas priscui to the Extremely Low Light Conditions of Lake Bonney, Antarctica ... - Poirier, Mackenzie (Université d'Ottawa | University of Ottawa, 2025)
À la demande de l'auteur, le résumé a été retiré en raison de la nature confidentielle de la thèse. Il sera ajouté une fois la période d'embargo terminée. At the author’s request, the abstract has been removed due to the confidential nature of the thesis. It will be added once the embargo period has passed. ...